Raman fiber lasers. (4th January 2017) - Supradeepa, V R; Feng, Yan; Nicholson, Jeffrey W
Abstract: High-power fiber lasers have seen tremendous development in the last decade, with output powers exceeding multiple kilowatts from a single fiber. Ytterbium has been at the forefront as the primary rare-earth-doped gain medium owing to its inherent material advantages. However, for this reason, the lasers are largely confined to the narrow emission wavelength region of ytterbium. Power scaling at other wavelength regions has lagged significantly, and a large number of applications rely upon the diversity of emission wavelengths. Currently, Raman fiber lasers are the only known wavelength agile, scalable, high-power fiber laser technology that can span the wavelength spectrum. In this review, we address the technology of Raman fiber lasers, specifically focused on the most recent developments. We will also discuss several applications of Raman fiber lasers in laser pumping, frequency conversion, optical communications and biology.